Penentuan Level Depresi Mahasiswa Tingkat Akhir Menggunakan Sistem Inferensi Fuzzy dengan Metode Sugeno - Tri Kesuma Pratiwi; Yuliani Puji Astuti (Universitas Negeri Surabaya, 2020)
Depression is a disease whose main symptoms are unclear and ambiguous. Depression has a wide influence on health, lifestyle and economic losses. Causes of depression can be seen from sleep disorders, uncomfortable environment, and excessive use of antidepressant drugs. This research determines the level of depression in the final year students who are in the thesis work phase, especially in the mathematics department of FMIPA UNESA, and implements it into fuzzy logic.This type of research is qualitative and quantitative. The inputs us Depression is a disease whose main symptoms are unclear and ambiguous. Depression has a wide influence on health, lifestyle and economic losses. Causes of depression can be seen from sleep disorders, uncomfortable environment, and excessive use of antidepressant drugs. This research determines the level of depression in the final year students who are in the thesis work phase, especially in the mathematics department of FMIPA UNESA, and implements it into fuzzy logic.This type of research is qualitative and quantitative. The inputs used are body mass index, systolic blood pressure and physical health questions. And the output produced is the severity of depression. Data collection techniques used by researchers by asking a number of questions that were asked to 40 final year students. And the processing stage uses the Sugeno fuzzy method. The results of this study can help improve medical services by determining the level of depression in students. This study uses the MATLAB application. The results of this system give an accurate valued are body mass index, systolic blood pressure and physical health questions. And the output produced is the severity of depression. Data collection techniques used by researchers by asking a number of questions that were asked to 40 final year students. And the processing stage uses the Sugeno fuzzy method. The results of this study can help improve medical services by determining the level of depression in students. This study uses the MATLAB application. The results of this system give an accurate value